ผลของการสนับสนุนทางสังคมต่อพฤติกรรมการให้นมมารดาของมารดาหลังคลอดก่อนกำหนด - ฐิติพร แสงพลอย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Mothers with preterm delivery risk breastfeeding failure due to health conditions of newborns and separation immediately after birth. This quasi-experimental research aimed to compare the breastfeeding behavior among mothers with preterm delivery between a control and an experimental group. The subjects consisted of 44 mothers with preterm delivery who admitted to delivery at Nakornping Hospital and Lamphun Hospital from May to November 2014. The subjects were purposively selected for the control group and the experimental group, with twenty-two in each group. The control group received routine postpartum care and the experimental group received both routine postpartum care and the social support plan for promoting breastfeeding behavior. The research instruments were 1) the Social Support Plan for Promoting Breastfeeding Behavior among Mothers with Preterm Delivery, 2) the Breastfeeding Manual for Mothers with Preterm Babies, and 3) the Breastfeeding Behavior among Mothers with Preterm Delivery Assessment. Data were analyzed using descriptive statistics, Chi-square test, Mann – Whitney U test and Wilcoxon matched pair test. The finding of this study revealed that mothers with preterm delivery in the experimental group had statistically significantly higher breastfeeding behavior scores than the control group (p < 0.001). The study results provide guidance for nurse-midwives to successfully support breastfeeding among mothers with preterm delivery.